Case analysis models in clinical ethics - López Barreda, Rodrigo (Acta Bioethica, 2015)
Advances in medicine cause every time with more frequency cases in which it is difficult to identify what is “the best or more accepted” from an ethical point of view. In order to solve these dilemmas, case analysis models and ethical foundation models are used. The analysis models require attention, because the identification of relevant information to issue an ethical judgment is difficult in some opportunities. This article tries to show some case analysis models of frequent use in Latin American bioethics and to make a comparative analysis of them. After a bibliographic review, six models used in clinical ethics are commented, showing the great diversity existing among them, as well as the existence of ignored factors which may interfere with the ethical decisions making process.